The tabular or multiple standard of value - Hepworth, L.G. (My University, 1897)
Introduction: With the development of modern industry the money question has been a question of constantly increasing importance. Under modern economics conditions money has many new and vastly more important functions to perform than formerly. Under a more primitive development, when trade was principally local, when the present state of division of labor was unknown, when commerce was carried on mainly by a system of barter, money prices had but little real meaning. But under the present system of division of labor and the constantly increasing interdependence of the units of industrial society, money has become the one principal agency of production whose object is to bring about the co-ordination of the various industrial elements of society, and we now consider the results of all industrial activities in terms of the monetary unit.
Citation: Hepworth, L.G. The tabular or multiple standard of value. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Economics; Industry; Money; Theses; Manuscripts (documents)